Influence of wall thickness on the fracture resistance of hollow zirconia artificial teeth fabricated by 3D zirconia printing - Kobayashi, Hiro; Rues, Stefan; Tasaka, Akinori; Rammelsberg, Peter; Yamashita, Shuichiro; Schwindling, Franz Sebastian (Journal of prosthodontic research, 2025)
Purpose: To determine the effect of wall thickness on the fracture load of hollow-structured zirconia teeth fabricated using 3D printing.Methods: The geometry of an artificial ceramic tooth (mandibular right first molar) was copied and modified. The final test group design yielded wall thicknesses of 0.30, 0.50, 0.75, and 1.00 mm. Twenty zirconia specimens from each group were fabricated using a 3D printer. Artificial teeth were divided into subgroups of teeth that remained hollow (hollow teeth) or were filled with resin (filled teeth). Fracture load tests were performed, and each artificial tooth was examined using a digital microscope. Analysis of variance was used to compare the fracture resistance of the artificial zirconia teeth among the conditions, followed by pairwise Tukey’s tests. T-tests were used to compare the fracture resistance between the hollow and filled teeth within the test groups.Results: The fracture resistance of artificial zirconia teeth decreased significantly (P < 0.001) with decreasing wall thickness. The mean fracture load reached ≥500 N for wall thicknesses of 0.75 mm and 1.00 mm. Resin filling of crowns significantly improved the fracture load of very thin walls. Microscopy revealed that most occlusal surfaces of the hollow teeth were completely fractured, whereas all the fracture surfaces of the filled teeth were incompletely fractured.Conclusions: Artificial zirconia teeth offer sufficient fracture resistance for clinical use when the wall thickness is ≥0.75 mm, regardless of the presence of resin filling.
Online veröffentlicht 3. Januar 2025
Gesehen am 15.08.2025